Digital Literacy as a Prerequisite for Achieving Good Academic Performance - Vrana, Radovan (2014)
The paper presents results from the research of students at the Faculty of Humanities and Social Science in Zagreb, Croatia about their perceptions and views on digital literacy. The results indicate that students recognize and relate the concept of digital literacy with a number of ICT supported activities in which they are involved on a daily basis at the university. Furthermore, the research showed that there is a connection between use of ICT and academic performance of the students in research. The students also exhibited a need for expansion of their current knowledge in a number of ICT related areas among which are many related to the content creation for the internet and multimedia. The research results will serve as an important component in the development of new or expanded university courses that include the use of ICT in any form.
ENG